Psychometric Features of a Scale for Characterizing Motivation for Academic Reading - Carla Muñoz Valenzuela; Schonemann Ferreira Torres; Pamela Sánchez Quintul; Sylvia Santander Pérez; Marcela Pérez Rodríguez; Jorge Valenzuela Carreño (Universidad Autónoma de Baja California, 2012)
The competencies associated with academic reading, especially the motivational aspects, are essential to undergraduate students' academic success. Motivation is an emerging issue that has given rise to many studies, yet motivation for academic reading remains a subject rarely addressed or studied. To effectively support the learning process, a diagnostic that is capable of providing precise, valid and reliable information on the motivational aspects of reading in an academic context is necessary. This article presents the results of the process of construction and validation of the Motivation Scale for Academic Reading (EMLA-acronym in Spanish), which was based on the Expectancy & Value model of Jacqueline Eccles and Allan Wigfield (2002), hereinafter EyV. This instrument provides clues for motivational intervention to incentivize reading in an academic context. Likewise, we also report on the structure of the instrument, its theoretical foundations, its factor structure and reliability-psychometric characteristics that make EMLA a solid, valid and reliable instrument.